Effects of the Fermi level energy on the adsorption of O2 to monolayer MoS2. (7th September 2018) - Klement, Philip; Steinke, Christina; Chatterjee, Sangam; Wehling, Tim O; Eickhoff, Martin
Abstract: Two-dimensional transition metal dichalcogenides possess large surface-to-volume ratios that make them ideal candidates for sensing applications such as detecting the surface adsorption of specific gas molecules. The resulting changes of the electrical and optical properties allow for detection and analysis of interaction mechanisms at the sensing interface. Specifically, we investigate the influence of O2 adsorption on monolayer MoS2 and the role of the Fermi level energy in this process. We record the response in photoluminescence and transport properties of monolayer MoS2 upon O2 adsorption and the impact of external electric gating. We find an increase of the photoluminescence intensity and a reduction of the conductivity upon O2 adsorption, and show that the adsorption can be enhanced by an increase of the Fermi level energy. These results demonstrate that ionosorption of O2 on MoS2 by charge transfer only occurs if free carriers are available in the conduction band of MoS2 . This free-carrier-supported adsorption-mechanism is corroborated by density functional calculations. Furthermore, the resulting reduction in screening of the Coulomb interaction between photo-excited electron–hole pairs amplifies the effect of the electron transfer on the excitonic recombination, causing a strong change of the photoluminescence intensity and rendering photoluminescence recording advantageous for sensing applications.